Hubungan Antara Bauran Pemasaran dan Kepuasan Konsumen Cau Chocolates Desa Marga, Kabupaten Tabanan - NI MADE JUNIARI; NYOMAN PARINING; PUTU UDAYANI WIJAYANTI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Relationship Between Marketing Mix and Customer Satisfaction of Cau Chocolates in Marga Village, Tabanan Regency This study aims to determine the level of consumer satisfaction seen from the marketingmix indicators and determine the effect of marketing mix indicators on customersatisfaction of Cau Chocolates in Marga Village, Tabanan Regency. This study usesdescriptive qualitative and quantitative methods with a total sample of 80 CauChocolates consumers determined using the purposive sampling method. The dataanalysis technique uses Structural Equation Modeling (PLS-SEM). The results showedthat the level of customer satisfaction Cau Chocolate produced a score of 3.63 whichwas included in the category of satisfaction. Meanwhile, the results of analysis usingSEM analysis produce, (1) product indicators positively and significantly influenceconsumer satisfaction, (2) price indicators positively and significantly influenceconsumer satisfaction, (3) place indicators positively and significantly influencesatisfaction consumers, and (4) promotion indicators have a positive and significanteffect on customer satisfaction.